2016
DOI: 10.1002/anie.201606269
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Methane‐Forming Reaction: Mechanism Confirmed Through Spectroscopic Characterization of a Key Intermediate

Abstract: Find your path: Methyl-coenzyme M reductase (MCR, turquoise) reversibly catalyzes the reduction of methyl-coenzyme M (methyl-S-CoM) with coenzyme B (CoB-SH) to form methane and the heterodisulfide. Recently, spectroscopic methods were used to detect trapped intermediates in a stopped-flow system, and CoM-S-Ni was identified after half a turnover of the MCR reaction (F =nickel porphinoid). This finding supports a methyl-radical catalytic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The key difference between them is how Ni(I) attacks methyl-S-CoM 82) (Figure 6c). Recent biochemical and spectroscopic analyses detected the latter intermediate, which strongly supports the methyl-radical mechanism (95,130). EPR and UV/visible spectroscopic data showed that only one of the two active sites of Mcr is active, suggesting cooperativity between them similar to that in an opposed piston engine (32,116).…”
Section: Catalytic Mechanismmentioning
confidence: 63%
“…The key difference between them is how Ni(I) attacks methyl-S-CoM 82) (Figure 6c). Recent biochemical and spectroscopic analyses detected the latter intermediate, which strongly supports the methyl-radical mechanism (95,130). EPR and UV/visible spectroscopic data showed that only one of the two active sites of Mcr is active, suggesting cooperativity between them similar to that in an opposed piston engine (32,116).…”
Section: Catalytic Mechanismmentioning
confidence: 63%
“…Moreover, they did not find any spectroscopic evidence for the methyl‐Ni III species, which is related to mechanism I. As discussed previously, the mechanistic picture of MCR is still incomplete and awaits further clarification.…”
Section: Ni‐dependent Enzymesmentioning
confidence: 86%
“…Carbon-nickel bonds had also been discussed as possible reaction intermediates in the mechanism of methyl coenzyme M reductase [103,104], but recent findings reveal a methyl radical intermediate [104,105]. Carbon-metal bonds have also been proposed in O 2 -tolerant, Cu-and Mo-dependent CO-oxidizing enzymes [106], which are unrelated to the anaerobic CODH depicted in Figure 1, but the case is unresolved.…”
Section: Carbon-metal Bonds In Ancient Metabolic Pathwaysmentioning
confidence: 99%